2005
DOI: 10.1111/j.1365-3156.2005.01432.x
|View full text |Cite
|
Sign up to set email alerts
|

Household pit latrines as a potential source of the fly Musca sorbens– a one year longitudinal study from The Gambia

Abstract: Summaryobjectives To assess whether the trachoma vector Musca sorbens was breeding in household latrines in a trachoma-endemic part of The Gambia.methods Longitudinal study of flies emerging from 16 sentinel household latrines selected at random from a list of all latrines present in four Gambian villages. Latrines were surveyed and fly traps were set over the drop hole for 24 h once per month for a year.results All the sentinel latrines were of the 'Gambian improved household latrine' design, which has a ceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 7 publications
2
30
0
Order By: Relevance
“…The first, and only, previous record of C. putoria in The Gambia was from one ‘modern’ lavatory in Sukuta, on the coast, in July 1952 [30]. The adults of C. putoria are morphologically similar to C. albiceps , and we think that recent descriptions of C. albiceps emerging from pit latrines in The Gambia [12] are likely to be mistaken; meaning C. putoria is the dominant fly in the country, not C. albiceps . Chrysomya putoria are known to breed in wet feces and can liquefy large fecal masses [31], which help break down feces and increase the longevity of latrines.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The first, and only, previous record of C. putoria in The Gambia was from one ‘modern’ lavatory in Sukuta, on the coast, in July 1952 [30]. The adults of C. putoria are morphologically similar to C. albiceps , and we think that recent descriptions of C. albiceps emerging from pit latrines in The Gambia [12] are likely to be mistaken; meaning C. putoria is the dominant fly in the country, not C. albiceps . Chrysomya putoria are known to breed in wet feces and can liquefy large fecal masses [31], which help break down feces and increase the longevity of latrines.…”
Section: Discussionmentioning
confidence: 82%
“…It was found to be the major fly species in a variety of latrine types in Botswana and Tanzania [11]. In The Gambia, an average pit latrine produces over 100,000 flies each year [12]. Of these flies, 97.8% were identified as Chrysomya spp.…”
Section: Introductionmentioning
confidence: 99%
“…M . sorbens preferentially breeds on human faeces left lying on the soil, with faeces in pit latrines of any kind, including “unimproved” latrines, not constituting a site for oviposition [32,33]. In our data, poor latrine access may simply be a surrogate for deprivation overall, with its associated limitations in economic and educational opportunities.…”
Section: Discussionmentioning
confidence: 95%
“…The presence of flies on faces has been well-documented as a risk factor for active trachoma in some environments [8], [29], [45] and there is evidence that the eye-seeking flies Musca sorbens (and possibly other domestic muscidae) are passive vectors in C. trachomatis transmission [45][48]. One study that examined fly density around used household pit latrines in The Gambia found that the majority of flies emerging from the latrine were Chrysomya albiceps , rather than M. sorbens [47]. We do not have data on the species of flies around pit latrines in Bijagós communities, however it is possible that there is ovipositioning by M. sorbens in or around latrines in these communities.…”
Section: Discussionmentioning
confidence: 99%